Mucopolysaccharidosis Type I and α-Mannosidosis—Phenotypically Comparable but Genetically Different: Diagnostic and Therapeutic Considerations - Marika Venezia; Martina Vinci; Paolo Colomba; Carmela Zizzo; Giovanni Duro; Marta Moschetti (Biomedicines)
Mucopolysaccharidosis type I (MPS-I) is an autosomal recessive, progressive, multisystem hereditary lysosomal storage disease (LSD), which is characterized by the gradual accumulation of dermatan sulphate (DS), heparan sulphate (HS), and glycosaminoglycans (GAGs) in all organs and tissues due to the deficiency of the enzyme α-L-hyduronidase. The multisystem clinical manifestations of varying severities of MPS-I are present in two forms—the “severe form of MPS I” (Hurler type) and the “attenuated form of MPS-I” (Hurler–Scheie or Scheie type). These forms represent the entire case history of the disease. The three phenotypes share common symptoms, including musculoskeletal abnormalities, facial dysmorphisms, hernias, short stature, finger stiffness, carpal tunnel syndrome, and corneal opacities. Abnormalities affecting the internal organs include hepatomegaly, splenomegaly, and valvulopathy. There is some evidence to suggest a similarity and overlap with the clinical symptoms of MPS-I, particularly in cases of another rare LSD that is autosomal and recessively inherited—l’α-mannosidosis. This disorder has been observed to result from a dysfunction of the corresponding α-mannosidase enzyme, which has been shown to lead to the accumulation of mannose-rich N-linked oligosaccharides. This review compares the phenotypic similarities and molecular differences between mucopolysaccharidosis type I (MPS-I) and α-mannosidosis. We review genotype–phenotype correlations, diagnostic difficulties, and the applicability of artificial intelligence for the assistance of differential diagnosis, with the goal of facilitating the earlier and more accurate diagnosis of these rare lysosomal storage diseases.